Broad consent for biobank research in South Africa - Towards an enabling ethico-legal framework - Mantombi Maseme; Jillian Gardner; Safia Mahomed (Global Bioethics)
Broad consent is permitted by the South African National Department of Health Ethics Guidelines but appears to be prohibited by section 13(1) of the Protection of Personal Information Act 4 of 2013. Additionally, the Act mandates that all personal data (including biobank sample data) be collected for lawful, explicit, and clearly defined purposes. There is possibility for ambiguity in interpretation because of this discrepancy between the two instruments. Given the association between the transfer of samples and data, the long-term nature of biobanking, which makes it impractical to provide too much or enough information because it is simply not available at the time of sample collection, and the various ways that the Protection of Personal Information Act 4 of 2013 have been interpreted, we aim to demonstrate that South Africa’s current regulatory framework should appropriately permit broad consent use for biobank research where the transfer of samples and their associated data are contemplated. In summary, the proposed amendments include removing regulatory ambiguity regarding broad consent use, ensuring adequate safeguards for research participants by specifying rules for data access and personal information processing, and incorporating consent form information requirements into the national Consent Template.